2007
DOI: 10.1021/ma071036f
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Alignment in the Aggregate Domains of Poly(9,9-dioctylfluorene) in Semidilute Solution

Abstract: The structure of poly(9,9-dioctylfluorene-2,7-diyl) (PF8) in deuterated toluene solutions at concentrations ranging from 0.60% to 7.0% (w/v) has been investigated by means of small-angle neutron scattering (SANS) and nuclear magnetic resonance (NMR) spectroscopy. PF8 chains exhibited aggregation above 1.0%, where the corresponding SANS profiles were characterized by the superposition of an aggregate component and a dynamic component associated with the transient network formed by interchain overlap. The 1H NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 46 publications
5
75
0
1
Order By: Relevance
“…41,67 During the cooling process, the β-phase content will greatly increase owing to the side-chain interactions. 68,69 When temperature decreases to 69-60°C, the single-layered β-sheet can be smoothly converted from isotropic phase according to our STM results, followed by the formation of cylinder clusters with a thickness of 14.9 nm via the sheetlike aggregate by SAXS. Because cylinder clusters effectively dominated the PFO-enriched phase, the extensive cross-linked networks are formed by the phase separation with isotropic polymer chains.…”
Section: ' Introductionsupporting
confidence: 67%
“…41,67 During the cooling process, the β-phase content will greatly increase owing to the side-chain interactions. 68,69 When temperature decreases to 69-60°C, the single-layered β-sheet can be smoothly converted from isotropic phase according to our STM results, followed by the formation of cylinder clusters with a thickness of 14.9 nm via the sheetlike aggregate by SAXS. Because cylinder clusters effectively dominated the PFO-enriched phase, the extensive cross-linked networks are formed by the phase separation with isotropic polymer chains.…”
Section: ' Introductionsupporting
confidence: 67%
“…9 We have shown that PF8 chains aggregated to form networks containing domains of aligned segments in the semidilute toluene solution. 15 In MCH the majority of PF8 chains were found to form bilayered sheetlike aggregates. The formation of these aggregates was often accompanied by the appearance of a mesomorphic β-phase in which the PF8 chains adopt the C β conformation.…”
Section: Introductionmentioning
confidence: 99%
“…22 The network-like structures are, moreover, observed for PF8/toluene mixtures at higher concentrations. 24 The role of side chain length in the formation of these assemblies remains unclear. Even though the effects of side chain length have been extensively studied for non-conjugated polymers such as polymers with a polymethacrylate main and polystyrene side chains, 25 the literature on the effects of side chain length on the phase behavior of PFs remains relatively sparse, consisting of basically comparison between PF8 and poly(9,9-dihexylfluorene) (PF6) 26 as well as poly(9,9-dihexylfluorene-alt-dialkoxybenzene) copolymers.…”
Section: Introductionmentioning
confidence: 99%